The Effect of Group Reference and Brand Trust on Purchase Decisions WithBuying Interest As Intervening Variables - Muhammad Fakhrul; Jusni Ambo Upe; Nuraeni Kadir (Hasanuddin Journal of Business Strategy, 2022)
This study aims to analyze the effect of reference groups and brand trust on purchasing decisions with buying interest as an intervening variable on consumers of HNI-HPAI herbal products in Bone. This study took data from 70 consumers of HNI-HPAI Healthy Homes in Bone. Data is then analyzed using Structural Equation Model (SEM) technique with the help of the SmartPLS3.0 program. The results of the analysis prove that the reference group and brand trust contribute to affecting purchasing decisions. Both reference group and brand trust were also found to have a positive effect on buying interest. Further, buying interest also has a positive and significant effect on purchasing decisions and was found to be able to mediate the relationship between the reference group and brand trust on purchasing decisions of HNI-HPAI consumers in Bone.